The Influence of Incentives and Non-Incentives Tax on Profit Management - Mujennah Mujennah; Safriansyah Safriansyah; Kevin Tanu (Center for Risk Management & Sustainability and RSF Press, 2021)
Disclosure of financial statement information for companies in Indonesia is very important, especially for stakeholders who do not have access to company information, especially in profit management, so that stakeholders are able to make the right decisions. Profit management is a managerial activity for management in influencing and interfering with financial statements. Public companies have benefited greatly because the effective tax rate of the company will become smaller so that the company is able to manage profits. Effective tax planning methods through tax incentives and non-tax incentives can help and provide convenience for companies in their profit management. Researchers want to find out how incentive taxes and non-incentive taxes affect profit management. The first results of the study showed that two variables of projected tax incentives with tax planning and deferred tax expense, as well as one variable non-incentive tax projected through leverage, had no effect on profit management. The second results of these studies showed that two other tax incentive variables were projected with the current tax expense and the number of shares paid, and the projection of one non-incentive variable of tax through variable capital intensity ratio had an effect on profit management. Researchers found difficulties when analyzing profit management since not all companies have positive test results against profit management values; there was a company with negative profit management values. The differences between this study to other researchers were the object and variable of research.